2021
DOI: 10.1007/s11332-021-00788-x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to vigorous physical activity and sedentary behavior changes in self-isolating adults during the COVID-19 pandemic in Brazil: a cross-sectional survey exploring correlates

Abstract: Background The COVID-19 pandemic imposed major changes on daily-life routine worldwide. To the best of our knowledge, no study quantified the changes on moderate to vigorous physical activity (MVPA) and sedentary behaviors (SB) and its correlates in Brazilians. This study aimed to (i) evaluate the changes (pre versus during pandemic) in time spent in MVPA and SB in self-isolating Brazilians during the COVID-19 pandemic, and (ii) to explore correlates. Methods A cross-sectional, retrospective, self-report onlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
6
50
2
2
Order By: Relevance
“…Studies from various countries have shown that during the COVID-19 pandemic physical activity (PA) decreased while sedentary behaviour increased. This was shown in various cross-sectional studies worldwide [4][5][6][7][8][9][10], and confirmed by several review articles [11,12]. Similar to international trends, studies from Austria have shown that during the COVID-19 pandemic, PA levels decreased by up to 48.9% [12,13].…”
Section: Introductionsupporting
confidence: 57%
“…Studies from various countries have shown that during the COVID-19 pandemic physical activity (PA) decreased while sedentary behaviour increased. This was shown in various cross-sectional studies worldwide [4][5][6][7][8][9][10], and confirmed by several review articles [11,12]. Similar to international trends, studies from Austria have shown that during the COVID-19 pandemic, PA levels decreased by up to 48.9% [12,13].…”
Section: Introductionsupporting
confidence: 57%
“…In response to the COVID-19 pandemic, many countries have implemented policies for social distancing and varying degrees of quarantine or isolation at home ( 13 ). Such strategies have had unintended negative effects on the functional fitness of older adults ( 33 , 34 ) due to decreased physical activity and increased sedentary behavior ( 14 , 15 ). Therefore, based on the results of this study, we propose that live-streaming home-based exercise programs may be an effective alternative method for increasing the functional fitness of community-dwelling older adults during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries have implemented policies for social distancing and varying degrees of quarantine or isolation at home ( 13 ). Such strategies further deteriorates the motivation for engagement in physical activity ( 14 , 15 ). Although conducting home-based exercises could be an alternative and a feasible method for eliminating barriers to engage in physical activity, one of the challenges of implementing home-based exercise training is the provision of instructions or feedback during the exercise intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only the self-reported decline in the physical activity volume was a predictor of self-reported decline in the emotional and mental health scores. The decreased physical activity level during social distancing has been appointed as one of the main causes of poor mental health (8,(22)(23)(24), followed by pandemic fear (25), and sedentary behavior (26). In fact, the best available evidence recommends increasing physical activity levels in this population to alleviate PD severity and to improve mental health (27).…”
Section: Factors Of Influence On Self-reported Clinical Worsening Due To Social Distancingmentioning
confidence: 99%